Troop 6000 : the Girl Scout troop that began in a shelter and inspired the world - Stewart, Nikita (Ballantine Books, 2020)
"Giselle Burgess, a young mother of five, and her children, along with others in the shelter, become the catalyst for Troop 6000. Having worked for the Girl Scouts earlier on, Giselle knew that these girls, including her own daughters, needed something they could be a part of, where they didn't need to feel the shame or stigma of being homeless, but could instead develop skills and build a community that they could be proud of. New York Times journalist Nikita Stewart embedded with Troop 6000 for more than a year, at the peak of New York City's homelessness crisis in 2017, spending time with the girls and their families and witnessing both their triumphs and challenges. Stewart takes the reader with her as she paints intimate portraits of Giselle's family and the others whom she met along the way. Readers will feel an instant connection and express joy when a family finally moves out of the shelter and into a permanent home, as well as the pain of the day-to-day life of homelessness. And they will cheer when the girls sell their very first cookies. Ultimately, Troop 6000 puts a different face on homelessness. Stewart shows how shared experiences of poverty and hardship sparked the political will needed to create the troop that would expand from one shelter to fifteen in New York City and ultimately to other cities around the country. Also woven throughout the book is a history of the Girl Scouts, and how the organization has changed and adapted to fit the times, meeting the needs of girls from all walks of life. Troop 6000 is the ultimate story of how when we come together, we can improve our circumstances, find support and commonality, and experience joy, no matter how challenging life may be." --